Recent advances in pharmacological treatment of psychiatric disorders - Rybakowski, Janusz (Przewodnik Lekarza/Guide for GPs, 2007)
During over half a century of contemporary psychopharmacology, five groups of psychotropic drugs have evolved, with therapeutic action on specific psychopathological states. They include: 1) antipsychotic (neuroleptic) drugs, with therapeutic action on psychotic symptoms such as delusions and hallucinations; 2) antidepressant drugs, exerting therapeutic action on depressive symptoms; 3) mood-stabilizing drugs, preventing manic and depressive recurrences in bipolar affective illness; 4) anxiolytic (anti-anxiety) drugs, having anti-anxiety and anti-stress properties; and 5) pro-cognitive (anti-dementia) drugs, causing an improvement of cognitive functions, especially memory. In the present paper, the use of these drugs in the therapy of psychiatric disorders is presented from a historical perspective and in the light of recent advances in clinical psychopharmacology at the beginning of the 21st century.